Speech Prosody 2018 2018
DOI: 10.21437/speechprosody.2018-172
|View full text |Cite
|
Sign up to set email alerts
|

Hand-clapping to the rhythm of newly learned words improves L2 pronunciation: Evidence from Catalan and Chinese learners of French

Abstract: Previous research has shown that rhythmic training enhances phonological speech processing (e.g., [1,2,3,4]). Yet little is known about whether rhythmic training can also help to improve pronunciation in a second language (but see [5,6,7]). This study tests the potential benefits of hand-clapping to the rhythm of newly learned French words for the acquisition of pronunciation patterns by Catalan children and Chinese adolescents. In two between-subjects experiments with a pretest and posttest design, participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…First, handclaps are suited to the temporal nature of Japanese—each clap can represent one mora. Further, handclapping has been found in general to be promising in previous studies of L2 pronunciation instruction (Baills et al., 2018; Zhang et al., 2018). Under McNeill's (1992) classification of gestures, handclapping may be considered both a metaphoric gesture and a beat gesture: It visually presents the underlying number of moras in the target word (metaphoric) but also expresses the rhythm of speech in Japanese (beat).…”
Section: The Current Studymentioning
confidence: 89%
See 1 more Smart Citation
“…First, handclaps are suited to the temporal nature of Japanese—each clap can represent one mora. Further, handclapping has been found in general to be promising in previous studies of L2 pronunciation instruction (Baills et al., 2018; Zhang et al., 2018). Under McNeill's (1992) classification of gestures, handclapping may be considered both a metaphoric gesture and a beat gesture: It visually presents the underlying number of moras in the target word (metaphoric) but also expresses the rhythm of speech in Japanese (beat).…”
Section: The Current Studymentioning
confidence: 89%
“…Third, Hirata et al. 's (2014) training included a vocabulary learning task as well as a phonological learning task, which might have caused cognitive overload (see e.g., Baills, Zhang, & Prieto, 2018), especially given that the participants were completely new to the language. Thus, there has been a need for studies that focus solely on the phonological property in question to maximize its possible efficacy.…”
Section: Background Literaturementioning
confidence: 99%
“…The results showed that observing beat gestures improved participants' pronunciation of the more difficult items. In similar studies, clapping hands to the rhythm of words has also been found helpful in improving L2 pronunciation (Baills et al, 2018;Zhang et al, 2018).…”
Section: Benefits Of Beat Gestures In L2 Vocabulary and Pronunciationmentioning
confidence: 79%
“…However, the experimental task of repeating a string of words for 10 minutes without any clear sentential meaning lacked ecological validity and may have led to boredom. Finally, an experimental study by Baills, Zhang, and Prieto (2018) found that handclapping to the rhythmic structure of words improved L2 pronunciation and a recent experimental study in a classroom setting by Iizuka, Nakatsukasa, and Braver (2020) found that hand-clapping benefitted the perception of segmental phonology, suggesting a potential role for providing rhythmic support in the learning of pronunciation.…”
Section: Songs and Singing For L2 Pronunciation Learningmentioning
confidence: 93%